Ethical surgical triage of patients with head and neck cancer during the COVID‐19 pandemic. Issue 7 (21st May 2020) - Civantos, Francisco J.; Leibowitz, Jason M.; Arnold, David J.; Stubbs, Vanessa C.; Gross, Jennifer H.; Thomas, Giovana R.; Sargi, Zoukaa; Casiano, Roy R.; Franzmann, Elizabeth J.; Weed, Donald; Perez, Cesar; Samuels, Michael; et al.
Abstract: Background: Coronavirus has serially overtaken our metropolitan hospitals. At peak, patients with acute respiratory distress syndrome may outnumber mechanical ventilators. In our Miami Hospital System, COVID‐19 cases have multiplied for 4 weeks and elective surgery has been suspended. Methods: An Otolaryngologic Triage Committee was created to appropriately allocate resources to patients. Hospital ethicists provided support. Our tumor conference screened patients for nonsurgical options. Patients were tested twice for coronavirus before performing urgent contaminated operations. N95 masks and protective equipment were conserved when possible. Patients with low‐grade cancers were advised to delay surgery, and other difficult decisions were made. Results: Hundreds of surgeries were canceled. Sixty‐five cases screened over 3 weeks are tabulated. Physicians and patients expressed discomfort regarding perceived deviations from standards, but risk of COVID‐19 exposure tempered these discussions. Conclusions: We describe the use of actively managed surgical triage to fairly balance our patient's health with public health concerns.